Transapical Deployment of Thoracic Stent Graft for Ascending Aorta Coronary Bypass Pseudoaneurysm in a Patient with Prosthetic Aortic Valve - Antonello, Michele; D'Onofrio, Augusto; Zavatta, Marco; Isabella, Giambattista; Maturi, Carlo; Piazza, Michele; Gerosa, Gino (AORTA, 2019)
The authors describe the transapical deployment of a thoracic endograft to exclude a saphenous vein graft proximal anastomotic pseudoaneurysm following coronary artery bypass grafting (CABG) in a 63-year-old male with a prosthetic aortic valve. A standard thoracic endograft has been deployed via transapical access after percutaneous transluminal coronary angioplasty of the native vessel perfused by the patent CABG. The procedure was uneventful; an 8-month computed tomography scan showed complete exclusion of the pseudoaneurysm with patency of supra-aortic trunks.
Keywords: transapical; ascending aorta; CABG pseudoaneurysm